Insect Management in Blueberries in the Eastern United States - Jay Cee L. Turner; Oscar E. Liburd (EDIS)
Revised! ENY-411, 15-page illustrated fact sheet by Jay Cee L. Turner and Oscar E. Liburd, describes several insect pests of blueberries. Includes references and a table of insecticides registered in Florida for use on blueberries. In this revision, several occasional insect pests are added, and references and pesticide recommendations are updated. Published by the UF Department of Entomology and Nematology, January 2007.